Signaling from Integrins to Fyn to Rho Family GTPases Regulates Morphologic Differentiation of Oligodendrocytes - Liang, Xiquan (J Neurosci, 2004)
Differentiation of oligodendrocyte progenitor cells requires activation of the Src family kinase Fyn. The signals that are upstream and downstream of Fyn in oligodendrocytes remain essentially unknown. Here we show that extracellular matrix engagement regulates the morphology of oligodendrocytes and activates Fyn. Infection of primary oligodendrocyte cultures with recombinant adenovirus revealed that expression of Fyn or its downstream target p190RhoGAP induced process extension. This phenotypic change was not observed when kinase-inactive Fyn or GAP-defective p190 mutants were expressed. Because Rho family proteins are regulated by p190, we monitored the effects of introducing dominant-negative (DN) or constitutively activated (CA) versions of Rho, Rac1, or Cdc42 into primary oligodendrocyte cultures. Expression of DN Rho, CA Rac1, or CA Cdc42 induced outgrowth of oligodendrocyte processes, whereas introduction of CA Rho, DN Rac1, or DN cdc42 inhibited oligodendrocyte differentiation, indicating that Rho and Cdc42-Rac1 exert opposing effects on oligodendrocyte differentiation. Direct measurement of Rho family activity revealed that RhoA was downregulated, and Cdc42 and Rac1 were upregulated during differentiation of primary oligodendrocytes. Moreover, inhibition of integrin engagement or of Fyn activation blocked activation of Rac1 and cdc42 as well as myelin basic protein expression. Taken together, these results suggest a linear signal transduction pathway of integrin-Fyn-Rho family GTPases that controls morphologic differentiation of oligodendrocytes.